2003
DOI: 10.1177/1046496403256011
|View full text |Cite
|
Sign up to set email alerts
|

Further Understanding of Trust and Performance in Virtual Teams

Abstract: Trust has been deemed to be critical in ensuring the efficient operation of virtual teams and organizations. This study empirically verifies ability and integrity as being antecedents of trust formation in virtual teams. However, effective team performance was found to be independent of the formation of trust. Further analysis suggests that information symmetry and good communication distinguish high performance teams from low performance teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(159 citation statements)
references
References 25 publications
6
129
0
2
Order By: Relevance
“…Some studies have found a positive relationship between the two (e.g., (Altschuller and Beneunan-Fich 2010)), while others have found no relationship (e.g., (Aubert and Kelsey 2003)). …”
Section: Trust and Performancementioning
confidence: 99%
“…Some studies have found a positive relationship between the two (e.g., (Altschuller and Beneunan-Fich 2010)), while others have found no relationship (e.g., (Aubert and Kelsey 2003)). …”
Section: Trust and Performancementioning
confidence: 99%
“…Trust will be a critical enabler of future military operations as individuals are forced to interact, communicate, and base life-threatening decisions on the inputs of distributed personnel. Past research has shown that trust facilitates information sharing (Kimmerle, et al, 2007), promotes team-oriented goals and perspectives (Dirks, 1999), and it reduces the costs associated with monitoring other team members (Aubert, & Kelsey, 2003). These characteristics are relevant for the current and future military operations.…”
Section: Trust and Military Team Performancementioning
confidence: 99%
“…For example, considerable evidence points to the critical role subteam dynamics play in the performance outcomes of intact teams (e.g., Aubert & Kelsey, 2003;Carton & Cummings, 2012;Lau & Murnighan, 2005;Liden, Sparrowe, & Wayne, 1997;Nirmala & Vemuri, 2009). Subteams tend to possess characteristics that differ from the intact team, which can have both positive and negative effects on the overall functioning and performance of the intact team.…”
Section: Teams and Family Businessesmentioning
confidence: 99%
“…Subteams tend to possess characteristics that differ from the intact team, which can have both positive and negative effects on the overall functioning and performance of the intact team. Family business leadership teams are likely to possess multiple subteams (e.g., family vs. nonfamily members, members of different generations, members from different linages within the family, or in-groups vs. out-groups), which can significantly influence team functioning and either promote or impede team performance (Aubert & Kelsey, 2003;Lau & Murnighan, 1998;Nirmala & Vemuri, 2009;Roussin, MacLean, & Rudolph, 2016;Tajfel, 1970). Other conditions, such as psychological safety (Edmondson, 1999; i.e., the shared belief within members that the team is safe for interpersonal risk taking), team reflexivity (Schippers, West, & Dawson, 2013; i.e., the extent to which teams collectively reflect on and adapt their working methods and functioning), team collaborative and competitive climates (Zhu, Gardner, & Chen, 2016), critical team member dispositional assertiveness (Pearsall & Ellis, 2006), and leader humility (Rego et al, 2017), to name just a few, can have important implications for exchange information, learning, creativity, and innovation within teams.…”
Section: Teams and Family Businessesmentioning
confidence: 99%